The power to change : mastering the habits that matter most - Groeschel, Craig (Zondervan, 2023)
"Craig Groeschel knows what it's like to be caught in the dispiriting cycle of trying to change, but failing. This was his story--until he began to discover practical principles for experiencing lasting change in his own life that he has taught to countless others for over twenty-five-plus years at LifeChurch"--